Soil bacterial communities associated with multi-nutrient cycling under long-term warming in the alpine meadow - Zhou, Xiaorong; Chen, Xianke; Qi, Xiangning; Zeng, Yiyuan; Guo, Xiaowei; Zhuang, Guoqiang; Ma, Anzhou (Frontiers in Microbiology, 2023)
Introduction The functions of terrestrial ecosystems are mainly maintained by bacteria, as a key component of microorganisms, which actively participate in the nutrient cycling of ecosystems. Currently, there are few studies have been carried out on the bacteria contributing to the soil multi-nutrient cycling in responding to climate warming, which hampers our obtainment of a comprehensive understanding of the ecological function of ecosystems as a whole. Methods In this study, the main bacteria taxa contributing to the soil multi-nutrient cycling under the long-term warming in an alpine meadow was determined based onphysichemical properties measurement and high-throughput sequencing, and the potential reasons that warming altered the main bacteria contributing to the soil multi-nutrient cycling were further analyzed. Results The results confirmed that the bacterial β-diversity was crucial to the soil multi-nutrient cycling. Furthermore, Gemmatimonadetes, Actinobacteria, and Proteobacteria were the main contributors to the soil multi-nutrient cycling, and played pivotal roles as keystone nodes and biomarkers throughout the entire soil profile. This suggested that warming altered and shifted the main bacteria contributing to the soil multi-nutrient cycling toward keystone taxa. Discussion Meanwhile, their relative abundance was higher, which could make them have the advantage of seizing resources in the face of environmental pressures. In summary, the results demonstrated the crucial role of keystone bacteria in the multi-nutrient cycling under the climate warming in the alpine meadow. This has important implications for understanding and exploring the multi-nutrient cycling of alpine ecosystems under the global climate warming.